2000
DOI: 10.1021/jp0017238
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular Decomposition of the 2-Oxepinoxy Radical:  A Key Seven-Membered Ring Intermediate in the Thermal Oxidation of Benzene

Abstract: The Gibbs free energy profiles for the unimolecular decomposition of the 2-oxepinoxy radical at temperatures ranging from 298 to 1250 K have been obtained using the B3LYP method. Intermediates and transition states have been obtained that link the 2-oxepinoxy radical to various products that have been experimentally observed during the thermal oxidation of benzene. The pathways explored include the rearrangement of 2-oxepinoxy radical to cyclopentadienyl radical, pyranyl radical, and various C4, C3, and C2 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 35 publications
4
46
0
Order By: Relevance
“…Most of the enthalpies of formation that we have calculated from the supplemental information by Hadad et al 15 are in agreement with the B3LYP, G3, and G3MP2B3 values reported across in Table III. There are, however, a few exceptions: as an example, a deviation of about 8 kcal mol −1 is observed for Y(C5)OC • DO, Y(C5O)C • DO, and p ‐ODY(C6)O • while the enthalpy data by Lin et al show agreement with our calculated G3 values.…”
Section: Resultssupporting
confidence: 88%
“…Most of the enthalpies of formation that we have calculated from the supplemental information by Hadad et al 15 are in agreement with the B3LYP, G3, and G3MP2B3 values reported across in Table III. There are, however, a few exceptions: as an example, a deviation of about 8 kcal mol −1 is observed for Y(C5)OC • DO, Y(C5O)C • DO, and p ‐ODY(C6)O • while the enthalpy data by Lin et al show agreement with our calculated G3 values.…”
Section: Resultssupporting
confidence: 88%
“…Single-point calculations were performed on optimized structures (neutral, anionic, and cationic) at DFT (B3LYP) levels with a 6-311þG(2d,2p) basis set. In all cases, we have verified that our DFT calculations produce negligible spin contamination, which is in agreement with other results reported in the literature [19,20]. To determine serine (Ser) amino acid relative acidity, deprotonation energy (DE) was calculated by deprotonating the H2 hydrogen atom, respectively (see Fig.…”
Section: Computational Detailssupporting
confidence: 89%
“…However, since the IR spectra calculated for various geometrical isomers of 6 are very similar, an assignment to one of the isomers was not possible. In a study by Fadden and Hadad for the ring-opening of 5 to ketoketene 6 a thermal activation barrier of 23.4 kcal mol À1 was calculated, [23] while two other rearrangements of 5 were found to proceed via considerably higher activation barriers. Our experiments do not allow us to determine if the ring-opening is a photochemical or a hot ground state reaction.…”
Section: Resultsmentioning
confidence: 99%